Application of lаrgе-sсаlе lіnguіstіс rеsоurсеs fоr the dоmаіn оntоlоgу extension (for the domain of «radiation safety») - Оробинская, Елена Александровна; Шаронова, Наталия Валериевна; Дорошенко, Анастасия Юрьевна; Шоша, Жан-Юг (Eastern-European Journal of Enterprise Technologies, 2014)
The paper proposes a new semi-automatic method, based on the NLP (natural language processing) principles for extension of the basic ontology (BO) for the domain of “Radiation Safety”. Using this method, existing BO was extended with new examples, found in the corpus and related to basic concepts by the relation of synonymy. Thus, the possibility and effectiveness of external linguistic resource for finding synonyms of the concepts of basic domain ontology in the text corpus was proved. The results have shown a high level of relevance. It was found in the experiment that pre-linguistic modeling and completeness of lexical resource play an important role for obtaining good results in the automatic extension of BO. This method can be considered as an important chain, still largely missing, necessary to raise the automatic ontology construction to a new level.